Morphological evolution of the Qingshuigou subaqueous delta of the Yellow River before and after the operation of the Xiaolangdi Reservoir (1997-2007) - Zhang, Jiarui; Wang, Qing; Zhan, Chao; Li, Zilu; Cao, Yin; Wang, Haojian; Liu, Zeyang; Yu, Limeng; Song, Qiuyu; Li, Yan; Su, Teng; Zhu, Jun; et al. (Frontiers in Marine Science, 2024)
The Modern Yellow River Delta has a rich history of geomorphological transformations shaped by frequent avulsions and rapid progradation. However, the delta entered a phase of altered morphodynamics following the construction of the Xiaolangdi Reservoir, which fundamentally restructured sediment transport regimes and seasonal hydrological patterns. These changes have amplified challenges in predicting long-term deltaic evolution under evolving boundary conditions. The Qingshuigou Subaqueous Delta, as a major depositional zone, provides a compelling lens to examine these morphodynamic processes. However, seasonal variations in riverine sand transport fluxes driven by the water-sand regulation scheme that accompanied the construction of the Xiaolangdi Reservoir and its impact on the evolution of the delta front are particularly understudied. This study developed a simplified long-term morphodynamic model of the Qingshuigou Subaqueous Delta to investigate its response to riverine water and sediment discharges from 1997 to 2007. The findings are as follows: (1) The morphological evolution of the Qingshuigou Subaqueous delta has gradually changed from the pattern of “leading edge deposition and localized near-shore erosion” before the construction of the Xiaolangdi Reservoir to the pattern of “enhanced leading edge deposition and increased near-shore erosion” after the construction. (2) The construction of Xiaolangdi Reservoir has weakened the spatial distribution of the erosion process to a certain extent, changing the spatial distribution dominated by the erosion process (63.8% of area) before the construction to the spatial distribution dominated by the accretion process (More than 50% of area) after the construction. (3) The spatial and temporal variability of the incoming sediments leads to a significant coarsening of the grain size of the tidal flats in the southern part of the abandoned delta, which in turn maintains a relatively steady state of the shoreline variability. In contrast, the abandoned sand spit experiences severe erosion and depositional fluctuations due to intensified wave action. (4) The study emphasizes the importance of considering seasonal variations in unsteady discharge in modeling the long-term evolution of the delta. It provides new insights into the spatial and temporal differentiation of the geomorphic equilibrium of the Yellow River Delta and contributes to a broader understanding of delta evolution.